2014
DOI: 10.1038/ng.3029
|View full text |Cite
|
Sign up to set email alerts
|

Common variants in the HLA-DQ region confer susceptibility to idiopathic achalasia

Abstract: Idiopathic achalasia is characterized by a failure of the lower esophageal sphincter to relax due to a loss of neurons in the myenteric plexus. This ultimately leads to massive dilatation and an irreversibly impaired megaesophagus. We performed a genetic association study in 1,068 achalasia cases and 4,242 controls and fine-mapped a strong MHC association signal by imputing classical HLA haplotypes and amino acid polymorphisms. An eight-residue insertion at position 227-234 in the cytoplasmic tail of HLA-DQβ1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 16 publications
6
90
0
8
Order By: Relevance
“…The ethnic homogeneity of the Central European patients and controls has been previously shown. 2 The distribution of females and males within each sample is presented in Supplementary Table 1. In all patients, achalasia diagnosis was made according to a standardized procedure, including esophageal manometry and/or esophagography.…”
Section: Sample Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ethnic homogeneity of the Central European patients and controls has been previously shown. 2 The distribution of females and males within each sample is presented in Supplementary Table 1. In all patients, achalasia diagnosis was made according to a standardized procedure, including esophageal manometry and/or esophagography.…”
Section: Sample Collectionmentioning
confidence: 99%
“…4 Previously, we have demonstrated that the imputation of the insertion show a high accuracy (concordance rate = 99.7%). 2 The data of the HLA-DQβ1 insertion was deposited to the European Genome-phenome Archive (EGA, http://www.ebi.ac.uk/ega/) and is available under accession number EGAS00001001515.…”
Section: Genotyping and Imputationmentioning
confidence: 99%
See 2 more Smart Citations
“…Achalasia is diagnosed in adults most frequently in the age group of 25 to 60 years with a male to female ratio in 1:1. [3,4] In this case, the patient is a 48 years old male active smoker. Patients usually suffered from dysphagia, regurgitation, difficulty in swallowing foods, chest pain, heartburn and weight loss.…”
Section: Discussionmentioning
confidence: 98%